HOUSEHOLD DEBT IN POLAND IN THE YEARS 2005-2017 – LEGAL ANALYSIS OF THE CASE OF SWISS FRANC LOANS. A CONTRIBUTION TO DEBATE - Żywicka, Agnieszka (Review of European and Comparative Law, 2018)
The subject of the article is the problem of the legal construction of loans denominated and indexed with a foreign exchange rate (CHF), which were incurred by Polish consumers in 2005-2017 and their repayment. The main problem analyzed in the article is the issue of repayment of franc loans noticed and analyzed both in scientific circles (by lawyers, economists, sociologists) and by politicians, which testifies to the significance and size of the phenomenon. This article will present individual views and proposals of the author in relation to Polish conditions, primarily from the legal point of view, the author firstly presents the legal construction of the loan, then presents the positions of banks and courts and proposes the cancellation of the contract and the conversion of some of its provisions.